INFLUENCE OF SPACE WEATHER ON A CARDIOVASCULAR SYSTEM OF A HUMAN BEING DURING VARIOUS SOLAR CYCLE PHASES - Samsonov, S. N.; Mavykina, V. I.; Krymsky, G. F.; Parshina, S. S.; Petrova, P. G.; Palshina, A. M.; Strekalovskaya, A. A.; Shadrina, L. P.; Vishnevsky, V. V. (Одеські астрономічні публікації, 2014)
The study of relationship of dynamics of space weather parameters to changes of cardiovascular system state of a human being was carried out by data of measurements of volunteer groups in October – December 2009 and March-April, 2011 by data ofYakutskand Tixie carried out according to the program of Russian-Ukrainian "Geliomed" project. It is shown that during a phase of minimum (2009) and growth phase (2011) of the 11-year solar activity a distinction in the response of cardiovascular system of a human being connected with the level of geomagnetic activity, latitude of residing of a human being and his/her age is observed.